2019
DOI: 10.3847/1538-4357/ab2fcb
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Quasar Light Echoes in 3D with Lyα Forest Tomography

Abstract: The intense radiation emitted by luminous quasars dramatically alters the ionization state of their surrounding IGM. This so-called proximity effect extends out to tens of Mpc, and manifests as large coherent regions of enhanced Lyman-α (Lyα) forest transmission in absorption spectra of background sightlines. Here we present a novel method based on Lyα forest tomography, which is capable of mapping these quasar 'light echoes' in three dimensions. Using a dense grid (10-100) of faint (m r ≈ 24.7 mag) background… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 125 publications
(169 reference statements)
0
27
0
Order By: Relevance
“…Although opacity fluctuations in the IGM arise mainly from density fluctuations, they are also affected by inhomogeneities in the ionizing radiation field, which are most profound in the vicinity of quasars. Schmidt et al (2019) showed that radiation from hyperluminous quasars might erase the flux deficit that otherwise would be produced by the surrounding matter overdensity. IGM tomography can then be used to trace quasar light echoes, providing a novel way to age date individual systems.…”
Section: Discussionmentioning
confidence: 99%
“…Although opacity fluctuations in the IGM arise mainly from density fluctuations, they are also affected by inhomogeneities in the ionizing radiation field, which are most profound in the vicinity of quasars. Schmidt et al (2019) showed that radiation from hyperluminous quasars might erase the flux deficit that otherwise would be produced by the surrounding matter overdensity. IGM tomography can then be used to trace quasar light echoes, providing a novel way to age date individual systems.…”
Section: Discussionmentioning
confidence: 99%
“…Quasar flickering can thus create an ionization "echo" in its surroundings. It has long been proposed to use this effect to accurately time the past radiative activity of luminous quasars by using the Lyα opacity toward background sources at small impact parameters (Adelberger 2004;Hennawi et al 2006;Visbal & Croft 2008;Schmidt et al 2019). We are now in a position to attempt such a measurement in practice.…”
Section: Quasar Timescalementioning
confidence: 99%
“…In our local sources model we have furthermore assumed isotropic AGN emission, and have ignored non-equilibrium ionization and light traveltime effects (e.g. Schmidt et al 2019). Finally, we have adopted a simple model for the distribution of LAEs in the transmission maps that does not include the effect of the local IGM opacity on Ly α emitter visibility.…”
Section: Protocluster Masses and The Correlation Between Laes And Ly α Transmission In Smoothed Mapsmentioning
confidence: 99%
“…Similarly, non-equilibrium photoionization and light traveltime effects due to flickering AGN emission may also result in gas that is less highly ionized (e.g. Oppenheimer & Schaye 2013;Schmidt et al 2019).…”
mentioning
confidence: 99%